NiCo2O4 nanoparticles rich in oxygen vacancies: Salt-Assisted preparation and boosted water splitting - He, Xiaobo; Dong, Yuanchu; Yin, Fengxiang; Li, Guoru; Zhao, Xinran (Frontiers in Chemistry, 2022)
NiCo2O4 is a promising catalyst toward water splitting to hydrogen. However, low conductivity and limited active sites on the surfaces hinder the practical applications of NiCo2O4 in water splitting. Herein, small sized NiCo2O4 nanoparticles rich in oxygen vacancies were prepared by a simple salt-assisted method. Under the assistance of KCl, the formed NiCo2O4 nanoparticles have abundant oxygen vacancies, which can increase surface active sites and improve charge transfer efficiency. In addition, KCl can effectively limit the growth of NiCo2O4, and thus reduces its size. In comparison with NiCo2O4 without the assistance of KCl, both the richer oxygen vacancies and the reduced nanoparticle sizes are favorable for the optimal NiCo2O4-2KCl to expose more active sites and increase electrochemical active surface area. As a result, it needs only the overpotentials of 129 and 304 mV to drive hydrogen and oxygen evolution at 10 mA cm-2 in 1 M KOH, respectively. When NiCo2O4-2KCl is applied in a symmetrical water splitting cell, a voltage of ~1.66 V is only required to achieve the current density of 10 mA cm-2. This work shows that the salt-assisted method is an efficient method of developing highly active catalysts toward water splitting to hydrogen.